2007
DOI: 10.1111/j.1471-0528.2007.01385.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of C‐reactive protein as a predictor of chorioamnionitis in preterm prelabour rupture of membranes: a systematic review

Abstract: Background Studies examining the use of C-reactive protein (CRP) as a predictor of chorioamnionitis in preterm prelabour rupture of membranes (PPROM) report highly conflicting results. Despite this, CRP is commonly used for the early diagnosis of chorioamnionitis.Objective To determine the diagnostic accuracy of CRP in the detection of chorioamnionitis in women with PPROM.Design Systematic review.Search strategy Studies were identified from MEDLINE , EMBASE (1974EMBASE ( -2006, PubMed and the Cochrane Library … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
87
1
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(108 citation statements)
references
References 25 publications
7
87
1
10
Order By: Relevance
“…Meanwhile, another systematic review of scientific work including 8 studies and 610 patients claims that there is no clear correlation between increased CRP levels and early diagnosis of chorioamnionitis. It is due to the fact that critical CRP values vary greatly from 5 to 40 mg/l (35). A study by Perrone et al did not prove any significant prognostic value of the WBC count, the same as our study (30).…”
Section: Discussionsupporting
confidence: 74%
“…Meanwhile, another systematic review of scientific work including 8 studies and 610 patients claims that there is no clear correlation between increased CRP levels and early diagnosis of chorioamnionitis. It is due to the fact that critical CRP values vary greatly from 5 to 40 mg/l (35). A study by Perrone et al did not prove any significant prognostic value of the WBC count, the same as our study (30).…”
Section: Discussionsupporting
confidence: 74%
“…This finding is in accord with some recently published data showing that measurement of PCT in maternal blood is unreliable in the clinical diagnosis of chorioamnionitis 2 . Despite conflicting evidence, our study showed significant elevation in maternal WBC and CRP in the chorioamnionitis positive group 12,13 . In our study, PCT was elevated in umbilical cord Table 2.…”
Section: Discussioncontrasting
confidence: 61%
“…12 Although maternal serum level of CRP slightly increases within gestational age, still this marker is used as an indicator of intrauterine infection, especially in pPROM cases [13][14][15][16][17][18] nevertheless reports that its benefits are conflicting. 19,20 On the contrary, there are only a few published data on CRP in vaginal fluid during pregnancy or its complications.…”
Section: Introductionmentioning
confidence: 99%